Binary and Chain Comparisons with an Experimental Linear Programming Food Price Index - Balintfy, Joseph L.; Neter, John; Wasserman, William (The Review of Economics and Statistics, 1970)
Joseph L. Balintfy, John Neter, William Wasserman, Binary and Chain Comparisons with an Experimental Linear Programming Food Price Index, The Review of Economics and Statistics, Vol. 52, No. 3 (Aug., 1970), pp. 324-330